2004
DOI: 10.1007/s00204-003-0534-z
|View full text |Cite
|
Sign up to set email alerts
|

A 13-week oral toxicity study of senna in the rat with an 8-week recovery period

Abstract: Senna was administered by gavage to Sprague Dawley rats once daily at dose levels of 0, 100, 300, 750 or 1500 mg/kg for up to 13 consecutive weeks followed by an 8-week recovery period for selected animals. Dose- and treatment-related clinical signs included abnormal feces, which were seen to varying degrees from animals at 300 mg/kg per day and more. Animals receiving 750 or 1500 mg/kg per day had significantly reduced body weight gain (males only) and, related to the laxative properties of senna, increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Likewise, a slight hyperplasia in the large intestine was observed. After an eight-week suspension of the use of the laxative, no histopathological anomalies were found, with the exception of the brown pigmentation of the kidneys [6]. …”
Section: Morphological Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a slight hyperplasia in the large intestine was observed. After an eight-week suspension of the use of the laxative, no histopathological anomalies were found, with the exception of the brown pigmentation of the kidneys [6]. …”
Section: Morphological Changesmentioning
confidence: 99%
“…Senna contains various anthranoids, where the most important are sennosides A and B; followed by aloe-emodin, emodin, and chrysophanol [6]. The sennosides, main active metabolite of senna, show a very low toxicity in rats [7] and their genotoxic activity in bacterial strains as well as mammal cells, in the cases where it was significant, was classified as weak [811].…”
Section: Introductionmentioning
confidence: 99%
“…1B, C), which indicated that constipation occurred in mice. Repeated senna administration caused functional intestinal disturbance20 and epithelial hyperplasia21. Therefore, it was suggested that structural change of the intestine was also caused in mice receiving senna.…”
Section: Discussionmentioning
confidence: 99%
“…The laxative property of Senna is based on two glycosides sennoside A and sennoside B [11]. The strongest laxative sennosides A and B, shows the lowest toxicity, while fraction that contains rhein 8-glycoside with a minimum efficiency laxative, has increased toxicity [12,13]. Emodin and aloe-emodin showed toxic effects on Salmonella typhimurium, on hepatocytes and fibroblasts from mouse [14].…”
mentioning
confidence: 99%
“…The presence of chemical compounds in the extract depended on the solvent that was used. In addition to that, the incubation process lead to the interaction of the compounds in the extract, as well as to the interaction with their metabolic products, which may have had first an inhibitory effect and later a stimulatory effect on cells at certain extract concentrations [12,13].…”
mentioning
confidence: 99%